The backstroke swimming start: State of the art - de Jesus, Ka.; de Jesus, Ke.; Fernandes, R. J.; Vilas-Boas, J. P.; Sanders, R. (Journal of Human Kinetics, 2014)
As sprint swimming events can be decided by margins as small as .01 s, thus, an effective start is essential. This study reviews and discusses the `state of the art` literature regarding backstroke start biomechanics from 23 documents. These included two swimming specific publications, eight peer-reviewed journal articles, three from the Biomechanics and Medicine in Swimming Congress series, eight from the International Society of Biomechanics in Sports Conference Proceedings, one from a Biomechanics Congress and one academic (PhD) thesis. The studies had diverse aims, including swimmers` proficiency levels and data collection settings. There was no single consensus for defining phase descriptions; and kinematics, kinetics and EMG approaches were implemented in laboratory settings. However, researchers face great challenges in improving methods of quantifying valid, reliable and accurate data between laboratory and competition conditions. For example, starting time was defined from the starting signal to distances as disparate as ~5 m to 22.86 m in several studies. Due to recent rule changes, some of the research outcomes now refer to obsolete backstroke start techniques, and only a few studies considered the actual international rules. This literature review indicated that further research is required, in both laboratory and competition settings focusing on the combined influences of the current rules and block configuration on backstroke starting performances